2007
DOI: 10.1149/1.2737347
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Approach to Investigate Low-Temperature Nanoscale Oxidation of Metals under UV Radiation

Abstract: The oxidation of metals at low temperatures is important not only from a fundamental point of view but also from technological relevance. Recent research has demonstrated that the nanoscale oxidation of metals such as Zr can be significantly altered during photon radiation. While there have been some experimental results to this effect, there are still no quantitative models to explain the enhancement in oxidation and the resulting self-limiting oxide thickness in the presence of radiation. In this paper, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Moreover, recent theoretical calculations have demonstrated that the field introduced by UV irradiation enhances the ionic diffusion in the oxide layer. 2,3 These results indicate that the UV irradiation may also be used to assist oxygen incorporation even at room temperature.…”
mentioning
confidence: 87%
“…Moreover, recent theoretical calculations have demonstrated that the field introduced by UV irradiation enhances the ionic diffusion in the oxide layer. 2,3 These results indicate that the UV irradiation may also be used to assist oxygen incorporation even at room temperature.…”
mentioning
confidence: 87%
“…14 Additionally, UV-light-induced high-field migration also enhances the ionic currents within the growing oxide film which comprises the electric field effect. 15 These photon effects result in significantly increased oxidation kinetics which can lead to atomic scale structural and morphological differences when compared to native-oxide films. Figure 10 shows the simulated oxide growth snapshots on Ni in the case of natural and photon-assisted oxidation.…”
Section: Pure Nickel Substratementioning
confidence: 99%
“…5 As mentioned earlier, the interaction of UV photons with molecular oxygen leads to the creation of activated atomic oxygen 14 and enhancement of the ionic currents within the growing oxide film by light-induced highfield migration. 15 Therefore, we study molecular and atomic oxidation of 5% Ni-Al substrates in the presence and absence of an external electric field. Oxidation kinetics enhancement due to externally applied electric field in case of metals such as Al is observed at electrostatic potentials approaching the Mott potential and higher.…”
Section: Ni-al Substratementioning
confidence: 99%
See 1 more Smart Citation
“…7 An important advantage of our approach is that it can be performed in a self-limiting manner by suitably controlling the temperature and oxygen partial pressure down to a monolayer. 14 We chose YDZ thin films as a model system for this study owing to its importance as a model oxygen-ion conductor, extrinsic nonstoichiometry, and band gap close to the photon energy used in this study. Ge was chosen as a model substrate because YDZ/Ge interface is abrupt and stable even after UV exposure.…”
mentioning
confidence: 99%